A Study of the Impact of Internet-Based Instruction Integrated Innovation Education on University Student Entrepreneurial Team Collaboration and Strategic Innovation - Zhao, Danqing; Zhong, Huaqian; Wu, Yingli; Zhou, Qianfu (Frontiers in Psychology, 2020)
Along with the approach of knowledge economy, the competition of comprehensive national power gradually becomes talent competition. The cultivation of innovative talents and the incubation of student entrepreneurial teams are the primary educational goals of universities being an important composition of national innovation system. University student entrepreneurial teams present the attribute of high technology and unique knowledge advantage. The persistent innovation of student entrepreneurial teams is attributed to knowledge playing the critical role. Especially, student entrepreneurial teams in the knowledge-based economic era, with speed, connection, and intangible value creation, have changed labor-intensive in the past into knowledge-intensive competition model. Taking university student entrepreneurial teams as the research object, total 500 copies of questionnaire are distributed and 386 valid copies are retrieved, with the retrieval rate 77%. Through the questionnaire survey, students' awareness, emotion, and will of innovation in innovation education are understood, and their cognition and intention of team cooperation and strategic innovation are investigated. The research results are concluded as followings. 1. Innovation education presents significantly positive correlations with collaboration. 2. Collaboration shows remarkably positive correlations with strategic innovation. 3. Innovation education reveals notably positive correlations with strategic innovation. According to the research result, suggestions are eventually proposed, expecting that university student entrepreneurial teams in China could acquire the advantage of technological innovation by applying the opportunities of broadband and wireless network infrastructure and developing innovative application and entrepreneurial model.